PERANAN NILAI-NILAI ISLAM DALAM MENINGKATKAN KEWIRAUSAHAAN DAN KINERJA USAHA MIKRO (Studi Di Kota Pekanbaru Provinsi Riau) - Musfialdy Musfialdy; M Soim (Lembaga penelitian dan pengabdian kepada masyrakat, 2017)
Micro-businesses have an important role in economic development, because the intensity of labor is relatively higher and a smaller investment, so that micro-businesses are more flexible in the face and adapt to market changes. This study aims to determine the role of Islamic values in promoting entrepreneurship and its impact on the performance of micro-enterprises. This research was conducted in the city of Pekanbaru in Riau Province with a sample size of 100 respondents. Data used include primary data and secondary data. To ascertain whether the instruments used in this research is accurately and reliably, there is validity and reliability test. After that normality test aims to test whether the data regression model has a normal distribution. Technical analysis of this study using SPSS software with path analysis. Micro-businesses, which is one type of business that is more involved in the community Riau province, especially in the city of Pekanbaru and become the foundation of many communities in the role of employment, and improving incomes and welfare. Noting this, it is necessary to conduct a study-you more in-depth about the adoption and implementation of Islamic values in shaping the entrepreneurial spirit, and improve business performance for the businessman. According to the research, the principal conclusions of this study are as follows: 1) Variable Values of Islam affect the Islamic entrepreneurship. The influence of these variables is positive relationship that is meaningful, that the understanding and implementation of Islamic values that encourage a micro business owners in the city of Pekanbaru implement Islamic entrepreneurship tend to be better. 2) The results of the analysis conducted in this study, obtained entrepreneurship variables significantly influence the performance of microenterprises with the thought that the higher understanding of entrepreneurship, will encourage the increased performance of micro-enterprises. 3) Values measured from the Islamic faith, worship and mu'amalat directly significantly affect the performance of micro-enterprises in the city of Pekanbaru. Hard work in the business that is based on sincere intentions, put my trust in God, and grateful for the sustenance of the work done is one of the factors increasing the performance of micro-enterprises in the city of Pekanbaru. The results of this study suggest that business must work hard and put their trust and an assurance to Allah SWT., As well as relationships between humans and the environment